Simultaneous determination of four bioactive compounds in Korean rice wine (makgeolli) by solvent extraction coupled with gas chromatography-mass spectrometry. Issue 1 (1st January 2018) - Lee, Jangho; Lee, Yunyeol; Ha, Jaeho; Yoo, Miyoung; Jang, Hae Won
ABSTRACT: Makgeolli is a traditional Korean rice wine reported to have anticancer, anti-inflammatory, and antioxidant effects. We developed an approach involving solvent extraction coupled with gas chromatography-mass spectrometry to determine four bioactive compounds, farnesol (FOH), squalene (SQ), and newly identified 4-vinyl guaiacol (4-VG) and 2, 4-di- tert -butylphenol (DTBP), in makgeolli . The method was validated with the linearity, limit of detection, limit of quantification, intra- and inter-day precision, and accuracy. The validated method was then applied to several makgeolli, beer, and wine samples. 4-VG and DTBP were identified in all beverages, but FOH and SQ were only identified in makgeolli.